Cagrilintide lowers bodyweight through brain amylin receptors 1 and 3Research in context - Alexandra Oliveira Carvas; Andrea Leuthardt; Patricia Kulka; Greta Lommi; Shad Hassan; Bernd Coester; Sofia Lundh; Tune Pers; Anna Secher; Kirsten Raun; Thomas A. Lutz; Christelle Le Foll (EBioMedicine)
Summary: Background: Amylin (AmyR) and calcitonin (CTR) receptor co-agonists are currently in Phase II/III clinical trials for obesity treatment. Amylin binds to a heterodimeric receptor composed of CTR and the receptor activity modifying proteins 1, 2 or 3 (RAMP1-3). Methods: We investigated the role of amylin 1 and 3 (AMY1R, AMY3R) receptors in modulating the pharmacological effects of the dual amylin–calcitonin receptor agonists, cagrilintide and salmon calcitonin (sCT), in RAMP1/3 knockout (KO) mice. Male wild-type (WT) and KO littermate mice were fed high-fat diet for 23 weeks prior to the 3-week treatment period with vehicle, 150 nmol/kg sCT or 3 nmol/kg cagrilintide (subcutaneously, SID). Findings: Body weight loss was observed in WT cagrilintide-treated mice (−3.4 ± 0.51 g, P < 0.005; n = 8/group), whereas sCT rather increased it (0.60 ± 0.38 g, P < 0.01; n = 8/group). The absence of RAMP1 and RAMP3 impeded cagrilintide's potency but improved sCT's efficacy on weight loss. Cagrilintide and sCT both decreased food intake during the first few days of treatment in WT mice only (Day 1: vehicle 2.7 ± 0.2 g; cagrilintide 1.2 ± 0.1 g, P < 0.0001; sCT 1.5 ± 0.2 g, P < 0.0021; n = 7–8/group). Both peptides activated cFos signal in neurons of the dorsal vagal complex (DVC) and lateral parabrachial nucleus (LPBN) of WT mice while AP cFos signal was decreased in cagrilintide-treated RAMP1/3 KO mice by 57% compared to WT cagrilintide-injected mice (P < 0.001, n = 5–6/group). Differential gene expression was analysed in the DVC, LPBN and mediobasal hypothalamic area of WT and RAMP1/3 KO mice. After 3 weeks of treatment, neither sCT nor cagrilintide significantly altered gene expression in the DVC or LPBN in WT mice. However, mRNA bulk sequencing points to a role of RAMP1/3 in synaptic function and receptor trafficking. Interpretation: Altogether, these results demonstrate the dependency of cagrilintide on AMY1R and AMY3R to lower body weight. Funding: This work was supported by an investigator led Novo Nordisk Consortium grant, Swiss National Foundation and the University of Zurich.